Tax credits, income support and partnership decisions - Dan Anderberg (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper considers the potential impact of welfare benefits on the partnership status of women in the UK. Using recent policy reforms to identify the response rate I find that a 100/week welfare benefit partnership penalty reduces the probability of a woman having a partner by seven percentage points. I also use the model to explore the potential effects of the recent Tax Credit reforms on partnership rates; I find that while the 1999 WFTC reform improved partnership incentives this effect was effectively undone by the 2003 WTC/CTC reform.
Keywords: H31; I38; J12; 330; welfare benefits; tax credits; family structure; Sozialer Wandel; Steuerbegünstigung; Familienleistungsausgleich; Soziale Beziehungen; Frauen; Ehe; Schätzung; Großbritannien